2003
DOI: 10.1002/gps.890
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Mini‐Mental State Examination for dementia screening among illiterate or minimally educated elderly Chinese

Abstract: Results suggest that in the socio-cultural context for Chinese, irrespective of their literacy skills, CAMSE proved feasible for use in clinical settings for dementia screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 28 publications
(31 reference statements)
5
58
0
1
Order By: Relevance
“…This study showed that the educational level, similar to previous results, significantly affect the MMSE score [11, 13,15,16]. The mean MMSE scores improved progressively with improvement in the education level from primary to higher levels in dementia group.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study showed that the educational level, similar to previous results, significantly affect the MMSE score [11, 13,15,16]. The mean MMSE scores improved progressively with improvement in the education level from primary to higher levels in dementia group.…”
Section: Discussionsupporting
confidence: 76%
“…The reason may be that most of control subjects in this study were educated as compare to dementia group. Xu et al calculated different cutoff score for educated and uneducated individuals [15].…”
Section: Discussionmentioning
confidence: 99%
“…21 A score of 20 on the MMSE was reported as an optimal cutoff point for illiterate or minimally educated elderly Chinese. 22 …”
Section: Hsieh Et Almentioning
confidence: 99%
“…There was no correlation between both scales and education 14,15 . There is a large amount of research on the correlation between education and cognitive per- formance, but our results could have two explanations: the tasks in these two scales are quite simple and there is a clear floor effect in control or less advanced dementia patients; the education bias might disappear at a relatively early stage of dementias.…”
Section: Discussionmentioning
confidence: 83%